Carsharing services with electric vehicles - Lim, Hong Shen (Nanyang Technological University, 2023)
Users purchasing and the usage of electric vehicles is increasing exceptionally and electric car has been encouraged in many countries including Singapore. Singapore goal is to to reduce our land transport emissions by 80% by the mid-century. Numerous policies were also introduced by the government to motivate users to use electric vehicles in Singapore. Out of many carsharing services that are available in Singapore, there are only a handful of services that offers Electric Vehicles, for example, BlueSG is known to be the first electric carsharing service that started in Singapore where the users have access to the application of electric vehicles that can be rented and shared at any point of the day. Only till recently, other carsharing services such as Get-Go have included electric vehicles into fleet of vehicles. Thus, this project aims to analyze the advantages and disadvantages of using electric vehicles as part of the carsharing services based on several factors – cost of rental between different applications, charging time and driving range of electric vehicle and environmental impacts of electric vehicles. The main mode of data collection will be through a survey that will be conducted online to collect the responses of people on their take on carsharing services with electric vehicles. Respondents were asked to list the problems they have encountered/faced when they use one of more popular carsharing application that uses electric vehicles – BlueSG and their take on the future of electric vehicles through carsharing services. The second survey was also conducted online where respondents were tasked to rank a few factors from the most important factor to the least important with regards to them choosing if they are willing to rent an electric vehicles just for car sharing. The results collected will then be modelled by using the Logistic Regression Model to create an equation that is linked to their choice of car sharing and the respective factors that are provided in the survey. The conclusion that we collated from all the survey results was that Location of where electric vehicles can be used for Car sharing has the highest influence while the convenience of finding electric vehicle for car sharing has the lowest influence on the choice of selecting electric vehicle for car sharing. Recommendations and suggestions were then introduced to try bring the usage of electric vehicles for car sharing up in Singapore based on the following results and will be presented at the end of this report.